Systematic Analysis of Cotton Non-specific Lipid Transfer Protein Family Revealed a Special Group That Is Involved in Fiber Elongation - Meng, Chengsheng; Yan, Yuanyuan; Liu, Zhengwen; Chen, Liting; Zhang, Yan; Li, Xiuxin; Wu, Liqiang; Zhang, Guiyin; Wang, Xingfen; Ma, Zhiying (Frontiers in Plant Science, 2018)
Non-specific lipid transfer proteins (nsLTPs) had been previously isolated from cotton fiber but their functions were unclear so far. Bioinformatic analysis of the tetraploid cotton genome database identified 138 nsLTP genes, falling into the eleven groups as reported previously. Different from Arabidopsis, cacao and other crops, cotton type Ⅺ genes were considerably expanded and diverged earlier on chromosome At11, Dt11 and Dt08. Corresponding to the type Ⅺ genes, the type Ⅺ proteins (GhLtpⅪs) all contained an extra N-terminal cap resulting in larger molecular weight. The research revealed that the expression of type Ⅺ genes was dramatically increased in fibers of tetraploid cotton compared with the two diploid progenitors. High-level of GhLtpⅪs expression was observed in long-fibered cotton cultivars during fiber elongation. Ectopic expression of GhLtpⅪs in Arabidopsis significantly enhanced trichome length, suggesting that GhLtpⅪs promoted fiber elongation. Overall, the findings of this research provide insights into phenotypic evolution of Gossypium species and regulatory mechanism of nsLTPs during fiber development.